2017
DOI: 10.11591/ijeei.v5i2.258
|View full text |Cite
|
Sign up to set email alerts
|

Computing Some Degree-Based Topological Indices of Graphene

Abstract: Graphene is one of the most promising nanomaterial because of its unique combination of superb properties, which opens a way for its exploitation in a wide spectrum of applications ranging from electronics to optics, sensors, and bio devices. Inspired by recent work on Graphene of computing topological indices, here we compute new topological indices viz. Arithmetic-Geometric index (AG2 index), SK3 index and Sanskruti index of a molecular graph G and obtain the explicit formulae of these indices for Graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The Sum connectivity index 34 introduced in 2009 has a major role in the QSPR studies. It has been found that the sum connectivity index has a close correlation with various physiochemical properties of alkanes such as boiling point, molar volume, molar refraction, heat of vaporization, surface tension and melting point 30,[35][36][37][38][39][40][41][42] . Therefore, there is a probability of having a correlation between more physiochemical properties.…”
Section: The Sum Connectivity Indexmentioning
confidence: 99%
“…The Sum connectivity index 34 introduced in 2009 has a major role in the QSPR studies. It has been found that the sum connectivity index has a close correlation with various physiochemical properties of alkanes such as boiling point, molar volume, molar refraction, heat of vaporization, surface tension and melting point 30,[35][36][37][38][39][40][41][42] . Therefore, there is a probability of having a correlation between more physiochemical properties.…”
Section: The Sum Connectivity Indexmentioning
confidence: 99%